Fostering Religious Character in Elementary School Students: Insights from Religious Habituation Activities - Supriyadi; Febriyanti, Berliana Khofifah (Indonesian Journal of Islamic Studies, 2023)
This qualitative phenomenological study explores the process of shaping the religious character of elementary school students through religious habituation activities both within and outside the classroom. Conducted at Hawari Creative Islamic Elementary School, Sidoarjo, with seven participants including religious teachers and grade 1 to grade 6 educators, the research identifies seven key habituation practices for strengthening students' religious character. These practices encompass praying before learning, memorizing Asma al-Husna, congregational Dhuha and Dhuhr prayers, memorizing juz 30, morning almsgiving, and reading surah al-Kahf. The study sheds light on the significance of these activities in religious character development, offering valuable insights for educators and researchers in the field of religious education. Highlights: Effective Religious Character Formation: This study provides insights into the efficacy of religious habituation activities in shaping the character of elementary school students. Multifaceted Habituation Practices: The research identifies and describes seven specific habituation practices, illustrating their role in religious character development. Educational Implications: The findings offer practical implications for educators and researchers seeking to enhance religious education strategies in elementary schools. Keywords: Religious habituation, Elementary school students, Character development, Qualitative approach, Phenomenology